Gastrointestinal Parasitism In Goats - Bionomics Of The Suprapopulation And Incidence In Young Goats - Israf Ali, Daud Ahmad (1991)

(untitled)
The Modified Parfitt's Technique (MPT) is used to assess the concentration of infective nematode larvae on pasture which gives an indication of the infection to which grazing animals are exposed . Validation of this technique showed that it was not successful when applied in the field and variation in results occurred among different grass species . Using Panicum maximum ( Guinea ) , Setaria sphacelata var splendida ( Setaria) and Digitaria setivalva (Mardi Digit) grasses , modifications were introduced to improve the larval recovery rate . The soaking of herbage in lukewarm water ( 38'C ) instead of tap water increased the recovery rate significantly without variation between the three grasses tested.Using this improved MPT , plot trials were conducted to assess the longevity of third-stage larvae ( L3 ) of goat trichostrongyles under the forementioned grass leys . However the technique failed to recover any L3 . Reasons for this were low number of larvae , rainfall , and larval - grass/debris adherence . There is a need for further investigation into this technique.